Hamstring strain injury in athletes - Martin, R. L.; Cibulka, M. T.; Bolgla, L. A.; Koc Jr., T. A.; Loudon, J. K.; Manske, R. C.; Weiss, L.; Christoforetti, J. J.; Heiderscheit, B. C.; Voight, M.; DeWitt, J.; Young, B.; et al. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Hamstring strain injury (HSI) may result in considerable impairment, activity limitation, and participation restriction, including time lost from competitive sports. This CPG includes sports-related overloading and overstretching injuries to myofascial or musculotendinous structures in any combination of the 3 hamstring muscles (the semitendinosus, semimembranosus, and biceps femoris).